2008
DOI: 10.1086/526404
|View full text |Cite
|
Sign up to set email alerts
|

Fallback and Black Hole Production in Massive Stars

Abstract: The compact remnants of core collapse supernovae - neutron stars and black holes - have properties that reflect both the structure of their stellar progenitors and the physics of the explosion. In particular, the masses of these remnants are sensitive to the density structure of the presupernova star and to the explosion energy. To a considerable extent, the final mass is determined by the ``fallback'', during the explosion, of matter that initially moves outwards, yet ultimately fails to escape. We consider h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
322
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(344 citation statements)
references
References 23 publications
20
322
2
Order By: Relevance
“…(Note that in Figure 16, we plot the corresponding gravitational mass for the neutron stars.) This simple analytical estimate is in agreement with the detailed numerical calculations of Zhang et al (2008), which are also shown in the figure. The green hatched region outlines the results for different compositions, explosion energies, and locations of the pistons for an assumed maximum neutron star mass of 2 M .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(Note that in Figure 16, we plot the corresponding gravitational mass for the neutron stars.) This simple analytical estimate is in agreement with the detailed numerical calculations of Zhang et al (2008), which are also shown in the figure. The green hatched region outlines the results for different compositions, explosion energies, and locations of the pistons for an assumed maximum neutron star mass of 2 M .…”
Section: Discussionsupporting
confidence: 88%
“…Fallback of stellar matter onto the collapsing core during the supernova explosion allows for the remnant to increase. However, this is also expected to increase the dispersion of masses by a comparable amount (see Zhang et al 2008), which is inconsistent with the narrowness of the inferred mass distribution of double neutron star masses. Considering a bimodal underlying distribution in the population of double neutron stars, as in Schwab et al (2010), makes the width of each distribution even narrower: 0.008 M and 0.025 M for the two components.…”
Section: Introductionmentioning
confidence: 91%
“…The remnant masses are the gravitational masses of the resulting neutron stars or black holes. They are based on the baryonic mass below the piston (i.e., the mass enclosed within a radius reaching out to the base of the oxygen shell at the presupernova stage) corrected for the binding energy ( Zhang et al 2007) according to the approximation given by Lattimer & Prakash (2001). In our study, none of the stars had any significant fallback after explosion.…”
Section: Variations In the Carbon Mass Fraction At Central Carbon Ignmentioning
confidence: 87%
“…The total mass accreted during this phase is more uncertain. Detailed 1D numerical simulations of the shock propagation and fallback estimate that typical values range from 10 −4 M to a few solar masses (Woosley et al 1995;Zhang et al 2008;Ugliano et al 2012). If more than a solar mass is accreted, the final outcome would be the delayed formation of a black hole, hours to days after core bounce.…”
Section: The Reverse Shock and The Fallback Scenariomentioning
confidence: 99%
“…If more than a solar mass is accreted, the final outcome would be the delayed formation of a black hole, hours to days after core bounce. Chevalier (1989) and Zhang et al (2008) showed that the accretion rate is expected to be maximum when the reverse shock reaches the NS and decreases as t −5/3 at later times. Therefore, the total amount of accreted mass is dominated by the fallback during the first few hours.…”
Section: The Reverse Shock and The Fallback Scenariomentioning
confidence: 99%